STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN SEBLAK CEU EDAH - Manggala, Gandara Muhammad Faradias; Maulani, Finna (Transpublika Publisher, 2022)
MSMEs are one of the backbone sectors of the economy in Indonesia. The MSME sector was able to survive the 1998 monetary crisis. The development of MSMEs has increased from year to year. This development occurs throughout Indonesia and including in the City of Tasikmalaya. This has become the government's attention to develop the MSME sector, including in terms of marketing. The increase in MSMEs occurred in all fields, including in the culinary field. One of the culinary fields that is developing is seblak. One of the long standings seblak in Tasikmalaya City is Seblak Ceu Edah. The marketing strategy carried out by Seblak Ceu Edah is a key in maintaining business, including during the Covid-19 pandemic. The research method used is qualitative research with a descriptive approach by conducting interviews and observations as primary data and documentation as secondary data. The results showed that there was an alignment of marketing strategies with the 4P method (product, price, place, and promotion) on the sales volume of Seblak Ceu Edah. The implication of the research that has been done is that it is expected to improve marketing strategies to increase sales volume of Seblak Ceu Edah.